IGFS 2014 Proceedings of the 3rd International Gravity Field Service (IGFS), Shanghai, China, June 30 - July 6, 2014 / edited by Shuanggen Jin, Riccardo Barzaghi. - Jin, Shuanggen.; Jin, Shuanggen.; Barzaghi, Riccardo.; Barzaghi, Riccardo. (International Association of Geodesy Symposia,, 2016)
This volume contains the proceedings of 24 peer-reviewed papers presented at the 3rd International Gravity Field Service (IGFS) General Assembly, which was organized by the International Gravity Field Service (IGFS), Commission 2 of the International Association of Geodesy (IAG), and Shanghai Astronomical Observatory (SHAO), Chinese Academy of Sciences. The Assembly was successfully held in Shanghai, China from June 30th to July 6th, 2014 with over 130 participants from 25 countries. The focus of the Assembly is on methods for observing, estimating and interpreting the Earth gravity field as well as its applications, including 6 sessions: gravimetry and gravity networks, global geopotential models and vertical datum unification, local geoid/gravity modelling, satellite gravimetry, mass movements in the Earth system and solid Earth investigations.